"I Love My Work, but This Is Not My Life": Women of Color in the Academy. Issue 2 (2nd July 2016) - Mena, Jasmine A.
Abstract : The present study used critical ethnography and intersectionality theory to better understand the experiences of Women of Color (WOC) in the academy. WOC experience numerous and significant challenges in the academy that have the potential to stifle their career growth. Claiming increased acceptance and diversity in the academy without a crystalline understanding of the lived experience of WOC is insufficient. The present article makes an important contribution by bringing attention to the experiences of WOC in the academy in their own voices. Thirteen staff and faculty WOC employed at a predominantly White mid-sized institution in the Northeast were interviewed. Overall, the findings indicate challenges to their credibility and competence as well as overt and covert oppressive experiences. In spite of the professional challenges they described, WOC devised coping strategies within and outside the academy that fostered professional perseverance. Implications and recommendations are discussed.